Utilization Factors of Groundnut Residues in the Integrated Cattle Farming System in Pujananting District Barru Regency - Hermimin; Sulfiana; Syamsinar; Helda Ibrahim (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2025)
This study aims to examine the utilization patterns of groundnut waste within the cattle integration system practiced by farming communities in Pujananting District, Barru Regency. The research was conducted from April to June. A descriptive quantitative approach was employed, with data collected through observation, questionnaires, and interviews with farmer-livestock breeders. The results show that groundnut waste, such as straw and peanut shells, is widely used as an alternative feed for cattle, either directly or through fermentation processes. The use of this waste is considered capable of reducing production costs by up to 30%. Furthermore, the integration system forms a sustainable agricultural cycle, in which livestock manure is reused as organic fertilizer for groundnut crops. This study reveals that the utilization of agricultural waste holds significant potential for improving efficiency, productivity, and the economic resilience of rural farmers. In addition to enhancing the efficient use of local resources, the integration system is circular in nature, where cattle manure serves as organic fertilizer for groundnut crops, thereby strengthening the sustainability of integrated farming systems in rural areas.